Ceramic spheroid and method for producing ceramic spheroid
By reasonably adjusting the CaO content and process parameters in the ceramic spherical body, a ceramic spherical body with high relative density, low monoclinic crystal ratio and low internal defect rate was created, which solved the problem of easy damage to the ceramic spherical body under high temperature conditions, and achieved stable crushing and dispersion effect under high temperature conditions.
Patent Information
- Application Number
- CN202380066232.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-02-14
- Filing Date
- 2023-09-13
- Publication Date
- 2025-04-29
AI Technical Summary
Under high temperature conditions at a liquid temperature above 60°C, ceramic spherical bodies are prone to damage during crushing and dispersion, and the prior art is difficult to effectively suppress such damage.
A ceramic spherical body with zirconia as the main component contains CaO of 3.5 mol% or more and 8.0 mol% or less, and is manufactured by a homogeneous pressurization (HIP) process such as granulation, sintering and heat, ensuring that the relative density of the ceramic spherical body is more than 99%, the monoclinic crystal ratio is less than 1 capacity%, the internal defect rate is less than 0.5%, and the surface roughness is less than 0.02 μm.
Even under high temperature conditions with liquid temperature above 60°C, the ceramic spherical body is not prone to damage, which significantly improves the stability of the medium during crushing and dispersion.
Smart Images

Figure BDA0005311922420000141
Abstract
Description
Technical Field
[0001] This invention relates to a ceramic sphere and its manufacturing method. Background Technology
[0002] In the micronization of powders used in electronic materials or the dispersion of pigments in inks, pulverizers such as ball mills, vibratory mills, sand mills, and bead mills that use pulverizing media are widely used. The pulverizing media such as balls and beads (hereinafter sometimes simply referred to as "media") that can be used in such pulverizers are ceramic sintered bodies with zirconium oxide as the main component, which exhibits excellent wear resistance and impact resistance.
[0003] In recent years, with the aim of improving the performance of crushed or dispersed materials, there has been a demand for further miniaturization, and consequently, the use of micro-diameter media with particle sizes of 300 μm or less is expanding. As a ceramic sphere that is not easily damaged even when crushing or dispersing such micro-diameter media at room temperature or high water temperature, a ceramic sphere has been proposed. This ceramic sphere is mainly composed of zirconium oxide, with a tetragonal crystal ratio of 80% to 95% by volume and a monoclinic crystal ratio of 5% to 5% by volume. Furthermore, the ceramic sphere is characterized in that, when the average particle size is X (μm), the maximum height fluctuation Wz (μm) at the intersection of the cross-section of the sphere with a diameter of X / 2 (μm) is 0.5% to 1.2% of the average particle size X (μm) (for example, see Patent Document 1).
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: International Publication No. 2022 / 044983 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] In recent years, there has been a trend towards higher speeds and shear rates in pulverization and dispersion processes to improve productivity and dispersibility, and the temperature of the dispersion medium has also tended to be higher. In particular, when using dispersion media containing hydroxyl groups, such as water, and pulverizing or dispersing at temperatures above 60°C, there is a problem of easy media deterioration and breakage such as cracks and gaps. Therefore, it is necessary to moderate pulverization and dispersion conditions by keeping the liquid temperature below 60°C, or to replace the medium before it breaks. While the ceramic spheres described in Patent Document 1 can suppress breakage during pulverization and dispersion, further suppression of breakage is required, especially at high temperatures above 60°C.
[0009] The purpose of this invention is to provide a ceramic sphere that is not easily damaged even when it is crushed and dispersed under high temperature conditions above 60°C.
[0010] Technical means to solve the problem
[0011] To address the aforementioned issues, the present invention primarily comprises the following structure.
[0012] (1) A ceramic sphere, with zirconium oxide as the main component, wherein the ceramic sphere contains more than 3.5 mol% and less than 8.0 mol% of CaO, has an average particle size of more than 0.01 mm and less than 0.3 mm, a relative density of more than 99%, and the proportion of monoclinic crystals obtained by powder X-ray diffraction is less than 1% by capacity.
[0013] (2) The ceramic sphere according to (1) contains 5.5 mol% or more and 8.0 mol% of the CaO.
[0014] (3) The ceramic sphere according to (1) contains more than 3.5 mol% and less than 6.0 mol% of the CaO.
[0015] (4) The ceramic sphere according to any one of (1) to (3), wherein the internal defect rate is less than 0.5%.
[0016] (5) The ceramic sphere according to any one of (1) to (4), wherein the surface roughness Sa is less than 0.02 μm.
[0017] (6) The ceramic sphere according to any one of (1) to (6), wherein the proportion of monoclinic crystals after a high-pressure cooking test at a temperature of 121°C and a humidity of 100% for 72 hours is less than 9% by volume.
[0018] (7) The ceramic sphere according to any one of (1) to (6) is used as a grinding medium for a bead mill apparatus and / or a ball mill apparatus.
[0019] (8) A method for manufacturing a ceramic sphere, comprising a method for manufacturing a ceramic sphere according to any one of (1) to (7), wherein the method for manufacturing the ceramic sphere comprises, in sequence, a granulation step, a sintering step and a hot isostatic pressing (HIP) step, wherein the granulation step is for granulating zirconium oxide powder having zirconium oxide as the main component and containing more than 3.5 mol% and less than 8.0 mol% CaO, the sintering step is for sintering the granulated body, and the hot isostatic pressing (HIP) step is for hot isostatic pressing the sintered body.
[0020] (9) The method for manufacturing ceramic spheres according to (8), wherein the heating temperature in the HIP process is 0°C to 75°C lower than the sintering temperature of the sintering process.
[0021] The effects of the invention
[0022] The ceramic spheres of the present invention exhibit the following effect: they are not easily damaged even when pulverized or dispersed at high temperatures above 60°C. Detailed Implementation
[0023] The ceramic spheres of the present invention are mainly composed of zirconium oxide and contain 3.5 mol% to 8.0 mol% CaO. Furthermore, in this specification, sintered bodies of zirconium oxide powder obtained as intermediates through one or more sintering processes, other than ceramic spheres, are sometimes collectively referred to as "intermediate sintered bodies." Additionally, both ceramic spheres and intermediate sintered bodies are sometimes collectively referred to and simply as "sintered bodies."
[0024] In this specification, "zirconia as the main component" means containing 90 mol% or more of zirconia. From the viewpoint of improving strength, it is preferable to contain 94 mol% or more of zirconia.
[0025] The ceramic spheres of the present invention are characterized by containing 3.5 mol% or more and 8.0 mol% of CaO. CaO acts as a stabilizer. When the CaO content is less than 3.5 mol%, the proportion of monoclinic crystals increases during sintering, and further increases when pulverized or dispersed at high temperatures above 60°C, thus making the medium prone to cracking, gaps, and other damage. When the CaO content is set to 5.5 mol% or more, monoclinic crystallization (stress-induced phase transformation) caused by collisions of the pulverized and dispersed materials can be further suppressed. Therefore, from the viewpoint of further suppressing wear during wet pulverization and dispersion, a CaO content of 5.5 mol% or more and 8.0 mol% is preferred. On the other hand, when the CaO content is more than 8.0 mol%, the main crystalline structure of the ceramic spheres becomes cubic, and the toughness decreases significantly. Therefore, when pulverized or dispersed at high temperatures above 60°C, collisions between the ceramic spheres easily lead to cracking and other damage. When the CaO content is set to less than 6.0 mol%, the ratio of cubic crystals can be suppressed, and the generation of cracks and notches caused by stress during crushing and dispersion can be further suppressed. Therefore, from the viewpoint of further suppressing cracks and notches during wet crushing and dispersion, it is preferable to have CaO content of 3.5 mol% or more and less than 6.0 mol%.
[0026] The content (mol%) of each component in the ceramic sphere can be determined as follows: First, the ceramic sphere is crushed using a universal testing machine. Approximately 0.3g of the crushed piece is placed in a platinum crucible and dissolved using potassium bisulfate. After dissolving in dilute nitric acid, the solution is determined, and each metal element is quantified using inductively coupled plasma (ICP) luminescence spectrophotometry. The determined metal element content is converted into oxides, then divided by the molecular weight of each component to obtain the mol%.
[0027] Besides CaO, other known stabilizers used in zirconium oxide powder include Y₂O₃, CeO₂, Al₂O₃, and MgO, with Y₂O₃ being the preferred stabilizer. However, since Y₂O₃ contains yttrium, a rare earth element, its supply is potentially unstable due to international circumstances. In this invention, since CaO is included as a stabilizer, it is preferable to omit Y₂O₃; specifically, the Y₂O₃ content is preferably 0.1 mol% or less.
[0028] The ceramic spheres of the present invention have an average particle size of 0.01 mm or more and 0.3 mm or less. As mentioned above, in recent years, there has been a demand for further miniaturization of the materials to be crushed or dispersed, and the use of micro-diameter media is expanding. However, when the average particle size is less than 0.01 mm, separation of the crushed or dispersed materials from the ceramic spheres becomes difficult. On the other hand, by having an average particle size of 0.3 mm or less, preferably 0.30 mm or less, the crushed or dispersed materials can be uniformly and micro-sized.
[0029] Here, the average particle size of the ceramic spheres can be determined using image analysis / measurement software after photographing the ceramic spheres. Specifically, the value is obtained as follows: An assembly of ceramic spheres is photographed using a digital microscope at magnification of 10x to 200x. Using image analysis / measurement software, the photographed image is binarized, using the brightness of the image as a reference. Circular patterns are separated from the binarized image using least-squares averaging, and the diameter of each separated circle is calculated as the diameter of each individual ceramic sphere. The average particle size is obtained by averaging the diameters of 1,000 randomly selected ceramic spheres.
[0030] As a method for setting the average particle size of ceramic spheres within the aforementioned range, methods such as classifying ceramic spheres by sieve grading can be cited as examples.
[0031] The relative density of the ceramic spheres of the present invention is 99% or higher. Relative density is an indicator of the degree of sintering, expressed as a percentage of the sintered density relative to the theoretical sintered density. When the relative density is less than 99%, the strength is insufficient due to inadequate sintering of the particles forming the ceramic spheres. Under high-temperature conditions (above 60°C), such pulverization and dispersion can easily lead to media breakage. A relative density closer to 100% is more preferable. Here, the relative density can be calculated using the following formula (1).
[0032] Relative density (%) = (sintered density / theoretical sintered density) × 100···(1).
[0033] The sintering density was determined using the Archimedes method as specified in Japanese Industrial Standards (JIS) Z8807:2012. The theoretical sintering density was calculated using the following formula (1-1).
[0034] Theoretical sintering density [g / cm³] 3 = 6.17 g / cm³ 3 -0.04 g / cm³ 3 [·mol%] × CaO molar concentration [mol%]···(1-1)
[0035] For example, if the CaO content is 3.5 mol%, then the theoretical sintered density is 6.03 g / cm³. 3 If it is 6.0 mol%, then it is 5.93 g / cm³. 3 If it is 8.0 mol%, then it is 5.85 g / cm³. 3 .
[0036] As a method to achieve a relative density of 99% or higher, for example, methods in the manufacturing method of ceramic spheres described later, such as setting the heating temperature or pressure in the HIP process to the preferred range described later, can be cited.
[0037] The proportion of monoclinic crystals in the ceramic spheres of the present invention, as determined by powder X-ray diffraction, is less than 1% by volume. When monoclinic crystals are present, they are prone to deterioration as a starting point during pulverization and dispersion at high water temperatures, thus easily causing breakage of the ceramic spheres. Therefore, from the viewpoint of preventing breakage, a lower proportion of monoclinic crystals is preferred. However, in the manufacturing process of ceramic spheres, wet grinding is generally performed to achieve surface smoothness. However, due to the stress exerted by the collisions between the ceramic spheres and each other or with the abrasive during wet grinding, the monoclinic crystal content is generally not completely reduced. In wet grinding, especially under conditions where the energy from the abrasive is reduced, both surface smoothing and a low monoclinic crystal ratio can be achieved.
[0038] As a method to make the proportion of monoclinic crystals less than 1% by capacity, for example, methods in the manufacturing method of ceramic spheres described later, such as making the sintering temperature or sintering time in the sintering process, the heating temperature in the HIP process, etc., within the preferred range described later, can be cited.
[0039] The internal defect rate of the ceramic spheres of the present invention is preferably 0.5% or less. Here, "internal defect" refers to cracks or pores inside the ceramic spheres. When the internal defect rate is 0.5% or less, the breakage of the ceramic spheres can be further suppressed when pulverizing and dispersing under high temperature conditions of liquid temperature above 60°C.
[0040] Here, the internal defect rate of the ceramic spheres can be determined by the following method. After grinding the ceramic spheres to 40%–60% of their diameter using a grinding machine, further fine grinding is performed for at least 10 minutes using a diamond slurry with a particle size of 6 μm to obtain a rough cross-section. The obtained cross-section is observed using a digital microscope at a magnification of 10x–200x. Defects are defined as those whose maximum length exceeds 20% of the sphere's diameter. Observe 200 randomly selected ceramic spheres, and calculate the proportion of ceramic spheres with defects as the internal defect rate.
[0041] As a method to reduce the internal defect rate to 0.5% or less, for example, methods such as setting the heating temperature or pressure in the HIP process within the preferred range described later in the method for manufacturing ceramic spheres can be cited.
[0042] The surface roughness Sa of the ceramic spheres of the present invention is preferably 0.02 μm or less. When the surface roughness Sa is 0.02 μm or less, wear during wet grinding and dispersion can be further suppressed.
[0043] Here, the surface roughness Sa of the ceramic sphere can be measured using a laser microscope and based on International Standardization Organization (ISO) 25178 (measurement method is JIS 0681-6:2014).
[0044] As a method to achieve a surface roughness Sa of 0.02 μm or less, for example, methods such as using a grinding device such as a tumbler grinder or a bead mill to grind the surface of a ceramic sphere can be listed.
[0045] The ceramic spheres of the present invention preferably have a monoclinic crystal content of 9% or less after undergoing a 72-hour pressure cooking (PCT) test at 121°C and 100% humidity. The PCT test under these conditions is an accelerated test simulating the state of pulverization and dispersion under high-temperature conditions above 60°C. When the monoclinic crystal content is 9% or less under these conditions, the increase of monoclinic crystals under high-temperature conditions above 60°C can be suppressed. Therefore, a high proportion of tetragonal crystals can be maintained, and the possibility of tetragonal crystals transforming into monoclinic crystals and expanding in volume under applied stress, leading to cracking of the ceramic spheres, can be suppressed. Therefore, even when pulverization and dispersion are performed under high-temperature conditions above 60°C, the breakage of the ceramic spheres can be further suppressed.
[0046] As a method to ensure that the proportion of monoclinic crystals after the PCT test is 9% or less, for example, methods such as setting the CaO content within the range described above, or methods of manufacturing ceramic spheres using preferred zirconia powder described later as a raw material, can be listed.
[0047] The ceramic spheres of the present invention are suitable for use as pulverizing media in bead mill devices, ball mill devices, etc.
[0048] The ceramic spheres of the present invention can be obtained by forming a raw material powder (hereinafter sometimes simply referred to as "raw material powder") with zirconium oxide as the main component and containing 3.5 mol% to 8.0 mol% CaO as the main component into a spherical shape and then sintering it. The preferred method for manufacturing the ceramic spheres of the present invention includes, in sequence, a granulation step, a sintering step, and a HIP (Hot Isostatic Pressing) step. The granulation step involves granulating zirconium oxide powder with 3.5 mol% to 8.0 mol% CaO as the main component; the sintering step involves sintering the granulated body; and the HIP (Hot Isostatic Pressing) step involves subjecting the sintered body to hot isostatic pressing. As described above, from the viewpoint of further suppressing wear during wet crushing and dispersion, it is preferable to use raw material powder containing 5.5 mol% or more and 8.0 mol% or less of CaO. From the viewpoint of further suppressing cracks and gaps during wet crushing and dispersion, it is preferable to use raw material powder containing 3.5 mol% or more and less than 6.0 mol% of CaO.
[0049] First, in the granulation process, raw material powder is used for granulation. Preferably, a rolling granulation method is used to form spherical particles. The rolling granulation method is a method in which raw material powder and a liquid binder containing binder and water are alternately added in a rotating drum to form spherical microparticles, and then the particles are grown by providing rotational linkage to the microparticles and powder, thereby producing spherical granules.
[0050] The preferred specific surface area, determined by the Brunauer-Emmett-Teller (BET) method of the raw material powder, is 20 m². 2 / g or more, the proportion of monoclinic crystals after the PCT test can be easily adjusted to the preferred range.
[0051] Since the obtained granules contain moisture, it is preferable to subject them to a drying process to remove the moisture inside the granules before the sintering process. During the drying process, it is preferable to use a dryer or similar device to gradually reduce the moisture content inside the granules.
[0052] Next, in the sintering process, the granulated body, which has undergone granulation and, if necessary, drying, is placed in a sagger or similar container and calcined in a furnace. This removes the binder and binds the raw material powder, resulting in a spherical ceramic sintered body. The preferred sintering temperature is 1250°C to 1300°C, and the preferred sintering time is 1 hour to 5 hours. By setting the sintering temperature above 1250°C, densification can be achieved, increasing the relative density. On the other hand, by setting the sintering temperature below 1300°C, the growth of primary particles can be moderately suppressed, and the proportion of monoclinic crystals can be reduced. Furthermore, even when pulverizing and dispersing at high temperatures above 60°C, the breakage of the ceramic spherical bodies is further suppressed.
[0053] Next, by simultaneously applying high temperature and isotropic pressure during the HIP process, defects such as voids or cracks remaining inside the spherical ceramic can be removed without altering its shape, further reducing the internal defect rate. Even when pulverizing and dispersing at high temperatures above 60°C, breakage of the ceramic spheres is further suppressed. Furthermore, when the HIP process is performed before the sintering process, the gas, acting as the pressure medium, penetrates the pores inside the relatively low-density granules and does not act as a force compressing the granules. Therefore, in this invention, it is preferable to supply the gas to the HIP process after the sintering process.
[0054] The HIP treatment is preferably performed within the range of Ts-75 (°C) to Ts, relative to the sintering temperature Ts in the sintering process. By setting the heating temperature in the HIP process to Ts-75 (°C) or higher, the diffusion of ceramic powders such as zirconia during the HIP treatment can be sufficiently promoted, further reducing the internal defect rate. The heating temperature is more preferably Ts-50 (°C) or higher, more preferably Ts-40 (°C) or higher, and even more preferably Ts-30 (°C) or higher. On the other hand, by setting the heating temperature in the HIP process to Ts or lower, the growth of primary particles can be moderately suppressed, as can the segregation of CaO to grain boundaries, and the proportion of monoclinic crystals can be reduced. The heating temperature in the HIP process can also be the same as the sintering temperature.
[0055] The pressure during the HIP process is preferably 100 MPa or higher. To achieve this high pressure, it is preferable to perform the HIP process in an Ar gas environment.
[0056] It is preferable to further grind the obtained ceramic spheres to reduce the surface roughness Sa, thereby obtaining a higher quality grinding medium. Examples of surface grinding devices include drum grinding devices, ball mill grinding devices, and bead mill grinding devices. In terms of achieving high circumferential speeds, bead mill grinding devices are preferred.
[0057] Furthermore, a grading process is preferred, which includes classifying the obtained ceramic spheres. This grading process allows the average particle size, minimum particle size, and maximum particle size to be within a desired range. Examples of grading methods include sieve grading using a mesh sieve. Sieve grading can also involve overlapping two sieves to separate relatively large coarse powder from relatively small fine powder in a single operation.
[0058] Example
[0059] The present invention will now be described in detail based on embodiments, but the invention is not to be limited by these embodiments. The evaluation methods in each embodiment and comparative example are as described below. Furthermore, the evaluation of calcium oxide content, average particle size, relative density, monoclinic crystal ratio, internal defect rate, monoclinic crystal ratio after PCT test, and the number of cracks caused by warm water air-running test were performed using ceramic spheres before surface grinding, while the evaluation of surface roughness and wear amount in barium titanate wet dispersion was performed using ceramic spheres after surface grinding.
[0060] (Calcium oxide content)
[0061] The ceramic spheres obtained from the various examples and comparative examples were crushed using a universal testing machine. Approximately 0.3 g of the crushed piece was placed in a platinum crucible and dissolved using potassium bisulfate. After dissolving in dilute nitric acid, the solution was determined, and the amounts of each metal element were quantified using ICP-N (Inductively Coupled Phosphorus) spectrophotometry. The determined amounts of metal elements were converted into oxides and then divided by the molecular weight of each component to obtain the mol%.
[0062] (Average particle size)
[0063] The ceramic spheres obtained in each example and comparative example were photographed using a VHX-2000 digital microscope (manufactured by Keyence, Inc.) at magnifications ranging from 10x to 200x. Using the image analysis / measurement software WinROOF (manufactured by Mitani Corporation), the background image and the image of the sphere were binarized and separated using brightness as a reference. Circular patterns were separated from the binarized image using least-squares averaging, and the diameter of each separated circle was calculated as the diameter of each ceramic sphere. The average diameter was calculated as the numerical average of the diameters of 1,000 randomly selected ceramic spheres.
[0064] (Relative density)
[0065] The sintering density of the ceramic spheres obtained from the various examples and comparative examples was measured using the Archimedes method as specified in JIS Z8807:2012. Furthermore, the theoretical sintering density was calculated using the following formula (1-1).
[0066] Theoretical sintering density [g / cm³] 3 = 6.17 g / cm³ 3 -0.04 g / cm³ 3 [·mol%] × CaO molar concentration [mol%]···(1-1)
[0067] The relative density of the ceramic spheres is calculated using the following formula (1) based on the sintering density and the theoretical sintering density.
[0068] Relative density (%) = (sintered density / theoretical sintered density) × 100···(1).
[0069] (Monoclinic crystal ratio)
[0070] The ceramic spheres obtained from the various examples and comparative examples were attached to the sample holder, and the diffraction intensity of each crystal phase was measured by wide-angle X-ray diffraction (micro-part X-ray diffraction). The measurement conditions are as described below.
[0071] Measuring device: MiniFlex 600 (registered trademark) (manufactured by Rigaku Corporation)
[0072] X-ray source: CuK rays (using a multilayer microscope)
[0073] Output: 50kV, 22mA
[0074] Slit system: 100μmφ pinhole
[0075] Measurement range: 2θ = 23°~33°, 70°~77°
[0076] Total time: 3600 seconds / frame.
[0077] Based on the measurement results, the monoclinic crystal ratio of zirconium oxide was calculated using the following formula.
[0078] Monoclinic crystal ratio (capacity%) = [{I m (111)+I m (1-1-1)} / {I m (111)+I m (1-1-1)+I t+c (111)}]×100
[0079] Here, I represents diffraction intensity. The subscripts m, t, and c represent monoclinic, tetragonal, and cubic crystals, respectively. The parentheses in the diffraction intensity represent the index of each crystal type.
[0080] (Internal Defect Rate)
[0081] After grinding the ceramic spheres obtained in the various examples and comparative examples to 40%–60% of their diameter using a grinding machine, they were further finely ground for at least 10 minutes using a diamond slurry with a particle size of 6 μm to obtain a rough cross-section. The obtained cross-sections were observed using a VHX-2000 digital microscope at a magnification of 10x–200x, and defects were defined as those whose maximum length exceeded 20% of the sphere's diameter. The proportion of ceramic spheres with defects was calculated as the internal defect rate by observing 200 randomly selected ceramic spheres.
[0082] (Surface roughness Sa)
[0083] For the surface-polished ceramic spheres obtained from the various embodiments and Comparative Examples 1 to 6, 8, a VK-X-150 laser microscope (manufactured by Keyence) was used for magnification observation with a 150x objective lens and digital zoom adjustment, so that the measurement range was (X / 3)μm×(X / 3)μm relative to the diameter X (μm) of the ceramic sphere being measured, and the arithmetic mean height Sa was measured. The arithmetic mean height Sa was measured for 10 randomly selected ceramic spheres, and the average value of the 10 values was calculated as the surface roughness Sa.
[0084] (Monoclinic crystal ratio after PCT test)
[0085] Ten g of ceramic spheres obtained from the various examples and comparative examples were inserted into a container and placed in a high-pressure steam testing machine (Hirayama PC-242HS, manufactured by Hirayama Corporation) at a temperature of 121°C and a humidity of 100% for 72 hours of exposure (PCT test). Then, after removing the residual moisture from the ceramic spheres, the monoclinic crystal ratio was calculated in the same manner as described in the (monoclinic crystal ratio) section.
[0086] (Number of cracks caused by the warm water air slide test)
[0087] 138g of ceramic spheres obtained from each of the examples and comparative examples 1 to 6 and 8 were filled into a bead mill apparatus (PCM-LR manufactured by Asada Iron Works Co., Ltd.), and the temperature was adjusted by maintaining 80°C with 300g of pure water. The mixture was circulated at a flow rate of 200mL / min and stirred at a circumferential speed of 12m / s for 10 hours.
[0088] After stirring, the ceramic spheres were removed and dried. One thousand randomly selected ceramic spheres were observed using a VHX-2000 digital microscope at magnifications of 10x to 200x to evaluate for the presence of cracks. The number of ceramic spheres with confirmed cracks was recorded as the crack count. Fewer cracks mean less likelihood of breakage, even under high-temperature pulverization and dispersion conditions above 60°C.
[0089] (Wear amount in barium titanate wet dispersion)
[0090] After performing the PCT test (monoclinic crystallinity after PCT test) on the surface-polished ceramic spheres obtained from Examples 1, 5-8 and Comparative Examples 1-2, 8, 138 g of the mixture was filled into a bead mill apparatus (PCM-LR manufactured by Asada Iron Works). A slurry prepared by dissolving 50 g of barium titanate (Sigma-Aldrich) and 10 g of dispersant (sodium dodecylbenzenesulfonate) in 1,000 g of pure water at 20°C was circulated and wet-dispersed for 3 hours at a circumferential speed of 12 m / s. The obtained slurry was filtered through a membrane filter with a 5 μm opening and dried in a hot air dryer at 90°C for 24 hours. The dried barium titanate powder was pulverized using a mortar and pestle, and the peaks of titanium, barium, and zirconium were determined using a fluorescence X-ray analysis apparatus (ZSX Primus II manufactured by Rigaku Corporation). The amount of zirconium oxide (ceramic spherical wear) in barium titanate powder is calculated based on the ratio of the intensity peak area of zirconium to that of titanium and barium.
[0091] [Example 1]
[0092] The specific surface area, determined by the BET method, is 22 m². 2 The obtained ceramic spheres have a molar ratio of calcium oxide / zirconia = 4.2 / 95.8. The raw material powder is “HSY-0481” manufactured by First Rare Element Chemical Industry (Group) Co., Ltd. The granules are granulated by rolling granulation until the average particle size after sintering is about 50 μm.
[0093] After drying the obtained granules, they were calcined at 1275℃ for 4 hours to obtain an intermediate sintered body (sintering process). Then, the intermediate sintered body was subjected to HIP treatment at 1275℃ and 120MPa for 1.5 hours (HIP process). The obtained sintered body was then sieved to obtain ceramic spheres with an average particle size of 0.05mm. The obtained ceramic spheres were then surface-polished using a wet bead mill at a circumferential speed of 14m / s with an abrasive for 10 hours.
[0094] [Examples 2-3]
[0095] Except for adjusting the size of the granules based on the rolling granulation method and the sieve grading method, and changing the average particle size as described in Table 1, ceramic spheres were made and surface-polished in the same manner as in Example 1.
[0096] [Example 4]
[0097] Except for changing the heating temperature in the HIP process as described in Table 1, ceramic spheres were made and surface-polished in the same manner as in Example 1.
[0098] [Examples 5-8]
[0099] Except for changing the raw material powder by changing the molar ratio of the obtained ceramic spheres to oxides as described in Table 1, ceramic spheres were made in the same manner as in Example 1, and the surfaces were ground.
[0100] [Comparative Example 1]
[0101] Except for not performing the HIP process, the ceramic spheres were made in the same manner as in Example 1, and the surfaces were ground.
[0102] [Comparative Examples 2-4]
[0103] Except for changing the heating temperature in the HIP process as described in Table 1, ceramic spheres were made and surface-polished in the same manner as in Example 1.
[0104] [Comparative Example 5]
[0105] Except for changing the sintering temperature in the sintering process and the heating temperature in the HIP process as described in Table 1, ceramic spheres were made and their surfaces were ground in the same manner as in Example 1.
[0106] [Comparative Example 6]
[0107] Except for HIP treatment at 1250°C and 120MPa for 1.5 hours followed by calcination at 1275°C for 4 hours, ceramic spheres were prepared and surface-polished in the same manner as in Example 1.
[0108] [Comparative Example 7]
[0109] In addition to using a specific surface area of 22 m² determined by the BET method. 2 Except for the raw material powder in which the molar ratio of calcium oxide / zirconium oxide in the obtained ceramic spheres was 8.6 / 91.4 (calcium oxide / zirconium oxide = 8.6 / 91.4), ceramic spheres were obtained in the same manner as in Example 1. The obtained ceramic spheres were then surface-ground using a wet bead mill, resulting in the ceramic spheres breaking.
[0110] [Comparative Example 8]
[0111] Yttrium chloride was added to zirconium oxychloride to achieve a molar ratio of yttrium oxide / zirconium oxide of 2.8 / 97.2 in the obtained ceramic spheres. A co-precipitation method was used to prepare spheres with a specific surface area of 9 m², as determined by the BET method. 2 / g of raw material powder.
[0112] Next, using the raw material powder, the shaped body is granulated using a rolling granulation method until the average particle size after sintering is about 50 μm.
[0113] After drying the obtained shaped body, it was calcined at 1400°C for 2 hours to obtain an intermediate sintered body (sintering process). Then, the intermediate sintered body was subjected to HIP treatment at 1380°C and 120 MPa for 1.5 hours (HIP process). For the obtained sintered body, ceramic spheres were made in the same manner as in Example 1, and the surfaces were polished.
[0114] The various embodiments and evaluation results are shown in Table 1. Comparative Examples 4 and 5 were destroyed by grinding, therefore the internal defect rate could not be determined. Furthermore, Comparative Example 7 cracked through surface grinding, therefore the cracking was obvious in the warm water air-running test, and surface roughness was not measured.
[0115]
Claims
1. A ceramic spherical body with zirconium oxide as a main component, the ceramic spherical body contains 3.5 mol% or more and 8.0 mol% or less of CaO, an average particle size of 0.01 mm or more and 0.3 mm or less, a relative density of 99% or more, and a proportion of monoclinic crystals measured by powder X-ray diffraction of 1 volume % or less. 2 . The ceramic spherical body according to claim 1 , comprising 5.5 mol % or more and 8.0 mol % or less of the CaO.
3. The ceramic spherical body according to claim 1, comprising 3.5 mol% or more and less than 6.0 mol% of the CaO.
4. The ceramic spherical body according to claim 1 or 2, wherein: The internal defect rate is less than 0.5%.
5. The ceramic spherical body according to claim 1 or 2, wherein: The surface roughness Sa is 0.02 μm or less.
6. The ceramic spherical body according to claim 1 or 2, wherein: The ratio of the monoclinic crystal after a high pressure boiling test for 72 hours under the conditions of a temperature of 121° C. and a humidity of 100% was 9% by volume or less.
7. The ceramic spherical body according to claim 1 or 2, used as a pulverizing medium for a bead mill and / or a ball mill.
8. A method for manufacturing a ceramic sphere, which is a method for manufacturing a ceramic sphere as described in claim 1 or 2, wherein the method for manufacturing a ceramic sphere comprises a granulation step, a sintering step and a hot isostatic pressing step in sequence, wherein the granulation step is to granulate a zirconium oxide powder having zirconium oxide as a main component and containing more than 3.5 mol% and less than 8.0 mol% of CaO, the sintering step is to sinter the granulated body, and the hot isostatic pressing step is to hot isostatic pressing the sintered body.
9. The method for producing a ceramic spherical body according to claim 8, wherein: The heating temperature in the hot isostatic pressing step is 0° C. to 75° C. lower than the sintering temperature in the sintering step.
Citation Information
Patent Citations
Ceramic spheres
WO2022044983A1